Evaluation of image quality in chest radiographs - Chand , R B; Thapa , N; Paudel , S; Pokharel , G B; Joshi , B R; Pant , D K (Journal of Institute of Medicine Nepal, 2013)
Introduction: Conventional chest radiography is a proven and a useful procedure for imaging of the main airways, lungs, mediastinum, heart, pleura and chest wall. The basic view is Postero- Anterior (PA) of chest in upright position. The role and importance of quality of radiograph is to help the radiologists and the clinicians in the diagnosis of diseases and its management. Thus it is important to show entire anatomical structure, respiration accuracy by counting 6 anterior ribs/ 10 posterior ribs, adequate penetration to see the lower thoracic intervertebral discs through the heart and scapula out of lung fields. The study is an attempt to quantify the quality of chest  radiographs by evaluating the quality of depiction of the anatomical and physical details.Methods: A cross sectional study was carried out from June to September, 2012 in Tribhuvan University, Teaching Hospital, Maharajgunj. Chest radiographs were collected in the scheduled examination days and evaluated by under the guidance of Radiologist. Five image criteria i.e. anatomical coverage, adequate inspiration, adequate penetration, rotation and scapula out of lung fields were categorized and descriptive statistics were calculated using SPSS version 11.5 software.Results: A total 1101 chest radiographs were collected from the radiology department for evaluation. Among them about 52.3% chest radiographs met all image criteria but remaining 47.7% did not meet these criteria due to inadequate arrested inspiration (34.8%), inadequate penetration (24%), rotation (21.8%), scapula not out of lungs field (14.7%) and no anatomical coverage (3.8%).Conclusions: The results identified that performing good quality chest radiograph according to Europcan guidelines is difficult. To a great extent the quality of chest radiographs depends upon skill of radiographer, equipment condition (x-ray machine, CR reader) and co-operation of patients. This is always challenging for radiographer and technologist.